The little book of currency trading : how to make big profits in the world of forex - Lien, Kathy, 1980- (Hoboken, N.J. : John Wiley & Sons, 2011)
The foreign exchange market, or forex, is now easily accessible to traders and investors around the world. Lien provides a firm understanding of how it works-- and how you can profit from it.
When lightning strikes -- Rubles and bahts and euros -- oh my! -- The A to Z of forex -- Step right up -- Movers and shakers -- The investor versus the trader -- What all winners do -- So you're an investor? -- So you're a trader? -- Risky business -- The top 10 mistakes -- Greetings from Nigeria, please help! -- Getting down to business -- Crash, burn, and learn -- Start smart.
rua 24/04/13
Loans
Keywords: Foreign exchange futures; Foreign exchange market